CONTESTING HEALING POWER AND KNOWLEDGE: HEALTH CARE IN KERALA'S PLURAL MEDICAL SYSTEM - VINEETHA MENON
The instrumentality of biomedicine in colonial empire has been the subject of many discussions. Western medicine or biomedicine was introduced in Travancore during the reign of Gowri Laxmi Bhai in 1811 when the British resident was very powerful. Of all the three major systems of medicine in Kerala, western medicine was the first to receive state patronage - even prior to the indigenous medical system of Ayurveda. Over the years biomedicine has developed rapidly to become the dominant medical system in Kerala. In the changing context of decentralized and localized development initiatives in Kerala, it is professed to salvage and resurrect sustainable local knowledge and resources. Therefore it is necessary to take a closer, critical and self-reflexive re-look at our health education, licensing practices of health care providers and drug policies with a historical appreciation.